UPAYA PEMBENTUKAN NILAI AGAMA ANAK RA UMMUL QURO WIJAYA MELALUI KEGIATAN MANASIK HAJI CILIK - muhammad fahrul roji nasution; Mukayat Al Amin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research was conducted at RA Ummul Quro Wijaya in Percut Sei Tuan District. This research discusses the role of Hajj simulation activities in shaping the religious values of early chilhood. This research aims to determine the role of the Hajj simulation activity on children’s religious values at RA Ummul Quro Wijaya. This research uses descriptive qualitative research involving two teachers. Data was collected thru interviews, observations, and documents. The data was analyzed qualitatively thru data collection, data reduction, data display, and drawing conclusions. Based on the results of this study, it shows that the positive impacts observed from this Hajj simulation activity are that children are able to learn about the fifth pillar of Islam, children are able to perform the pillars of Hajj, children are able to learn about religion from an early age, and this will accustom children to doing good deeds. The Hajj ritual activity in shaping religious values in children is also influenced by supporting and hindering factors.